Techno-economic scenario analysis of containerized solar energy for use cases at the food/water/health nexus in Rwanda - Annelise Gill-Wiehl; Isa Ferrall; Serena N. Patel; Samuel B. Miles; Jodie Wu; A. Newman; Daniel M. Kammen (Development Engineering, 2023)
Containerized' infrastructure solutions have the potential to power the needs of under-resourced communities at the Food/Water/Health nexus, particularly for off-grid, underserved, or remote populations. Drawing from a uniquely large sample of identical containerized solar photovoltaic energy deployments in Rwanda ("Boxes" from OffGridBox), we estimate the potential reach and impact that a massive scale-up of such a flexible, modular approach could entail for fast-growing yet resource-constrained communities around the world. This analysis combines modeled and in-the-field data to consider three use cases (water, food, and health), across optimistic and realistic scenarios. We estimate pollution externalities and compare this solution to incumbent technologies, incorporating uncertainties. In our optimistic scenarios, this containerized solution could provide for either 2083 individuals' daily drinking water needs, 1674 individuals' daily milk consumption, or 100% of a health clinic's energy demand. We then quantify the added benefit of providing these loads using solar energy instead of the incumbent non-renewable diesel generator in terms of cost and air quality, and incorporate the sensitivity of results to uncertainties using Monte Carlo Analysis simulations. For water purification and milk chilling uses, we find that solar has a lower lifecycle cost of energy; 0.39 and 0.38 USD/kWh respectively compared to 0.63 [range: 0.52, 0.80] USD/kWh and 0.59 [range: 0.48, 0.76] USD/kWh for diesel. Additionally, solar has lower cost variability and avoids pollutant and greenhouse emissions (e.g., 85,799.08 kgs [range: 66,830.49, 115,491.30] of carbon dioxide over the 20-year system lifetime). Moving beyond the standard energy modeling of previous literature, this analysis is uniquely able to inform future sustainable energy systems at the Food/Water/Health nexus.
Keywords: 330; Containerized energy solutions; Food/water/health nexus; Energy access; Renewable energy; Air pollution